The Failure of Ambition To Be a Queen as Seen in Phillipa Gregory’s The Other Boleyn Girl - Helmita Helmita; Ayunanda Putri (Jurnal Ilmiah Langue and Parole, 2018)
The Other Boleyn Girl is a historical novel written by British author Philippa Gregory loosely based on the life of 16th century aristocrat Mary Boleyn (the sister of Anne Boleyn) of whom little is known. Inspired by Mary’s life story, Gregory depicts the annulment of one of the most significant royal marriages in English history and conveys the urgency of the need for a male heir to the throne. The writer took Anne Boleyn’s ambition to become a queen as a center of the thesis. Technique of collecting data of this analysis is by library research. It means that the writer applies the data which the writer takes from library and other written material from book store, internet or even motion picture. In analyzing this data, the writer uses psychological theories by Sigmund Freud. Sigmund Freud’s psychoanalytic theory of personality argues that human behavior is the result of the interactions among three component parts of the mind: the id, ego, and superego. This theory, known as Freud’s structural theory of personality, places great emphasis on the role of unconscious psychological conflicts in shaping behavior and personality. The result show that although it’s good to have ambition to drive someone to reach their goal to succeed but ambition without limit could destroy everything and everyone around you. And it even could destroy yourself too.